The effect of the acetylator phenotype on the metabolism of sulphasalazine in man - Khan, A K Azad (1983)
The metabolism of sulphasalazine (SASP) has been studied in three series of patients with ulcerative colitis. In the first series, 185 patients were studied serially for 1 to 3 years while being maintained on treatment with 2 g SASP daily. This showed that the slow acetylators were liable to have high serum concentrations of sulphapyridine (SP) whereas the concentrations of SASP and of 5-aminosalicylic acid (5-ASA) were not appreciably different in the fast and slow acetylators. In the second series, 170 patients were admitted to a therapeutic trial designed to elicit the optimum dose of SASP for maintenance therapy. The patients were allotted at random to treatment with 1, 2, or 4 g daily for a period of 6 months. The bigger the dose of SASP the more effective was the treatment, but side effects were common with the bigger doses. The common symptomatic side effects of nausea, malaise, and headache were associated with high circulating levels of total SP and were almost always confined to the slow acetylators. Minor haematological effects were common and were dose related. With the exception of methaemoglobinaemia they were related to the circulating level of free SP and hence were more common among the slow acetylators. By contrast, methaemoglobinaemia was correlated with the circulating level of acetylated sulphapyridine and hence was more common among the fast acetylators. In the third series, 36 patients on maintenance treatment with 2 g SASP daily were given prednisolone in a dose of 20 mg daily for one week and dummy tablets for one week, these two treatments being applied in random order. The prednisolone had no appreciable effect on the serum concentration of SASP and its metabolites, but it increased the percentage acetylation to a small extent in both fast and slow acetylators.